Features of the cortical activity of men having a nigh or lov alpha-frequency background of the EEG while performing alternate finger movements - Tsos, Anatolii V.; Kotsan, Ihor Ya.; Morenko, Alevtyna H.; Цьось, Анатолій Васильович; Коцан, Ігор Ярославович; Моренко, Алевтина Григорівна (Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, 2014)
The purpose of this paper is to identify the cerebral electrical activity features in men with a high or low α-frequency background while performing the alternate ϐinger movements. A test group consisting of 104 healthy men from the ages of 19 to 21 was divided into two groups according to the magnitude of their individual α- frequency (ІАF) median – groups with high (n = 53, IAF ≥ 10,04 Hz) and low (n = 51, IAF ≤ 10,03 Hz) levels of ІАF. Changes in power and the coherence of the EEG oscillations during the alternate ϐinger movements as well as intergroup differences were evaluated. Men with high a IAF are distinguished by higher rates of speed and accuracy in terms of their sensory-motor response. The role of inhibitory neural processes increases in the case of men whose frequencies are low. The implementation of alternating ϐinger movements in male groups is accompanied by a decrease in the coherence of θ-, α1-, α3- EEG oscillations in the cortex in general, β- and γ-activity - in the rear temporal and occipital areas. In the frontal and central lobes of α2-, β- and γ- ranges an increase in EEG coherence ϐluctuations was observed. The power of θ-, α- and β1- waves, especially in the posterior cortex areas, decreases. A larger degree of low-frequency ϐluctuations in EEG power can be observed in the frontal area. Thus, more economical brain processes providing the processing of any sensory or motor information in men with a high IAF determine higher levels of the speed and accuracy of their sensorimotor responses. Men with a low IAF have lower ductility but a higher voltage of brain processes correlated with a decrease in the sensorimotor response of speed capabilities increasing the role of inhibitory effects.
Keywords: power; coherency; electroencephalogram; individual alpha-frequency; alternate movements by ϐingers